Modeling complex mobile web applications from UI components : Adding different roles and complex database design - Vera, Pablo Martín (2013)
Component Based Hypermedia Design Method (CBHDM) is a modeling methodology that allows creating mobile web applications by designing and configuring user interface components. Starting from models this methodology performs two transformations to finally generate the application source code using the MDA approach. In order to configure the user interface components this methodology creates a custom language that´s powerful enough for designing complex applications. This paper shows how to configure components for allowing complex database design and also includes a new feature on the model supporting different user roles assigning different screens to operate the system.